Fatores de proteção social no enfrentamento da violência: dar voz e vez aos adolescentes em seu ambiente escolar - Santos, Angela Letícia dos (2010)
School violence constitutes one of the difficulties in the accomplishment of the knowledge building process, fact which worries and drives educators, and also students, to deepen the understanding of the forms to react to the problem. This work studies the social condition of schools, which, built around a repression system, end up being a space favorable to the manifestation of violent attitudes, often destroying attempts for breaking free from hierarchization by the students. From the references in Foucault and related to the accumulation of the theoretical debate about bullying and from the contribution of the ethical discussion and of the relative presence of the family in the educational framework and in the social protection, we proceeded to the observation of the consequences of this system. In the research work performed, through qualitative procedures, with state schools students from the municipality of São Bernardo do Campo/SP, the reports reinforce the Idea of a repressive school system: they point to the power relationships in the schools, among school officials, teachers and students; to the disrespect to the singularities and condition of the developing individual; to the abuse of punishment, such as school suspension and mandatory transference; to the reinforcement of prejudice and permanence of segregation. The identification of the multiple causes that concur to establish violent conditions, after the analysis of the bibliography and content of the reports from the students, served as base to point out useful protection factors for the improvement for living together in the schools. Guidelines to be adopted by educators in their everyday actions derive from them. Thirteen of them are presented: Promoting education with ethics; To be an effective educator; To be a rational educator; Knowing the stages of the infant and youth development; To respect to be respected; To recognize the differences and diversities to built relationships of respect; To be fair; To identify unfairness against children and teenagers; To stimulate political participation; To be solidary; To involve the community in the educational process; To repudiate violence and lead the transforming dialogue